2013
DOI: 10.1016/j.molcel.2013.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Transcriptional and Translational Repression of p53 by TGF-β1 Impairs the Stress Response

Abstract: Summary Cellular stress results in profound changes in RNA and protein synthesis. How cells integrate this intrinsic, p53-centered program with extracellular signals is largely unknown. We demonstrate that TGFβ1 signaling interferes with the stress response through coordinate transcriptional and translational repression of p53 levels, which reduces p53-activated transcription, and apoptosis in precancerous cells. Mechanistically, E2F4 binds constitutively to the TP53 gene and induces transcription. TGFβ1-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Such technologies will be critical for examining individual cells from tissue biopsies of heterogeneous populations. For example, we recently identified that TGF-β1 signaling represses the gene expression program induced by DNA damage, and our immunohistochemistry studies revealed heterogeneity of this phenomenon in different cancer cells present in the same tumor (44). Although not all rare variants are relevant to personalized cancer treatment, some have the potential to drive drug resistance or serve as biomarkers of therapeutic success.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Such technologies will be critical for examining individual cells from tissue biopsies of heterogeneous populations. For example, we recently identified that TGF-β1 signaling represses the gene expression program induced by DNA damage, and our immunohistochemistry studies revealed heterogeneity of this phenomenon in different cancer cells present in the same tumor (44). Although not all rare variants are relevant to personalized cancer treatment, some have the potential to drive drug resistance or serve as biomarkers of therapeutic success.…”
Section: Discussionmentioning
confidence: 90%
“…Briefly, 25,000 cells were plated in each well of 12-well plates and after 24 h were treated with vehicle-ethanol or up to 100 nM paclitaxel-containing media. After 4 d, cells were fixed with 10% formaldehyde, and the IC 50 was established by Giemsa staining (44). Cell number was plotted as a percent of cells relative to vehicle control with SE from four replicated wells from a representative experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanism by which p53 expression in stromal cells is regulated by proteins secreted from cancer cells currently remains unknown. One possibility is that TGF-β contributes to the downregulation of p53 because it activates normal fibroblasts to support cancer and repress p53 expression through the induction of MDM2 (31,32). Alternatively, cancer-derived exosomes may also be involved in down-regulating p53 expression in stromal cells because cancer cells release exosomes expressing specific proteins and RNAs to influence the expression of various proteins (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence found cis-platinum treatment of MDA-MB-231 breast cancer cells increased both TgF-β mRNA levels and the secretion of active TGF-β, which enhanced growth arrest that facilitated repair of damage, thus rendering these cells resistant to cis-platinum killing (41). In the report of López-Díaz et al, TGF-β was shown protected cells from DoxR, 5-fluorouracil and paclitaxel-induced cell death specifically though Smad 4-mediated complex (42). Moreover, TgF-β pretreatment was able to attenuate the TAM cytotoxic effect and decrease the apoptosis ratio in breast cancer (43).…”
Section: Emt-related Cytokines and Drug Resistance In Breast Cancermentioning
confidence: 94%